Program Barisan Pejuang Subuh (BPS) sebagai Upaya Revitalisasi Musala dan Penguatan Kepemimpinan Mahasiswa - Muhammad Ashadi Rasyad; Adrian Yudabangsa; Zaidan Zikri Malem; Muhammad Furqan (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Musholla as a community prayer space plays a strategic role in fostering spiritual and social development; however, many mushollas experience low attendance, particularly during Subuh prayer. The Barisan Pejuang Subuh (BPS) Program was implemented as an effort to revitalize musholla and strengthen students’ leadership in religious practices. This community service activity was conducted at Musholla Husnul Yaqin, Meurandeh Teungoh Village, on November 14, 2025, using a participatory approach through congregational Subuh prayer led by students, a religious sermon delivered by a lecturer, and communal breakfast with worshippers. Data were collected through observation, informal interviews, and documentation. The results indicate increased congregation attendance, positive community responses, and improved student confidence and competence in leading prayers. The program also strengthened social interaction between students and the community. It is recommended that the BPS program be implemented sustainably by involving musholla management and village authorities and expanded through follow-up activities such as regular Subuh studies and leadership training for youth.